The Effect of Hydrostatic Pressure on the Performance of Oscillating Wave Surge Converter - Prabowo, Anton Dwi; Julian, James; Wahyuni, Fitri; Purba, Riki Hendra; Toding Bunga, Nely (Fakultas Teknik Universitas Pancasila, 2025)
The latest energy demand increasingly drives innovation in ocean wave energy technology, including the Oscillating Wave Surge Converter (OWSC). This consider analyzes the impact of water profundity varieties on the execution of OWSCs put on the seabed. The study was conducted numerically using the Boundary Element Method by testing four variations of air depth at wave periods between 1.2 and 2.8 seconds and wave amplitudes of 0.1 meters. The results show that the optimal depth, equivalent to the flap height (D2), produces the highest maximum displacement due to the balance between hydrostatic pressure and wave energy the flap receives. Conversely, depths that are too shallow (D1) or too deep (D4) result in smaller displacements due to the instability of the movement in shallow air and the attenuation of wave energy in deep air. In addition, more extended wave periods tend to decrease the changing cycle frequency but increase the symmetry of the flap movement at a certain depth.